Tree growth of dipterocarp plantation forest in Java, Indonesia - Mindawati, N.; Heriansyah, I.; Hiratsuka, M.; Toma, T.; Gintings, A.N.; Morikawa, Y. (2004)
The objective of this study was to show the growth performance of dipterocarp plantations. The authors collected data on diameter at breast height and total height of the trees in four research forests established between 1937 and 1955. In total, 29 species of Dipterocarpaceae were examined. The results verified that dipterocarp species would be the target species for timber production with relatively long-rotation periods, and also suggested a high potential for timber production by man-made forests of Dipterocarpaceaein Java.